Book Scavenger - Chambliss Bertman, Jennifer (New York : Henry Holt and Company, 2015)
Just after twelve-year-old Emily and her family move to San Francisco, she teams up with new friend James to follow clues in an odd book they find, hoping to figure out its secrets before the men who attacked Emily's hero, publisher Garrison Griswold, solve the mystery or come after the friends.
"Christy Ottaviano Books."
810
Keywords: Treasure hunt (Game) -- Juvenile fiction; Books and reading -- Juvenile fiction; Publishers and publishing -- Juvenile fiction; Moving, Household -- Juvenile fiction; San Francisco (Calif.) -- Juvenile fiction; Adventure fiction